2016
DOI: 10.1038/srep26247
|View full text |Cite
|
Sign up to set email alerts
|

An efficient algorithm to identify the optimal one-bit perturbation based on the basin-of-state size of Boolean networks

Abstract: Boolean networks are widely used to model gene regulatory networks and to design therapeutic intervention strategies to affect the long-term behavior of systems. In this paper, we investigate the less-studied one-bit perturbation, which falls under the category of structural intervention. Previous works focused on finding the optimal one-bit perturbation to maximally alter the steady-state distribution (SSD) of undesirable states through matrix perturbation theory. However, the application of the SSD is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Edge-reverse: This mutation represents a switch in both the type and outcome of a molecular interaction or relationship between two proteins or genes [ 58 ]. In other words, both the activation/inhibition relationship and the output value of an interaction are switched.…”
Section: Methods and Implementationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Edge-reverse: This mutation represents a switch in both the type and outcome of a molecular interaction or relationship between two proteins or genes [ 58 ]. In other words, both the activation/inhibition relationship and the output value of an interaction are switched.…”
Section: Methods and Implementationsmentioning
confidence: 99%
“…Edgetic mutations have been recently considered in experimental studies to better reveal genotype-to-phenotype relationships and drug discovery [ 15 , 16 ]. Some in silico studies have also been conducted [ 57 , 58 , 67 ]. For example, Li, Long [ 57 ] investigated the dynamic properties and stability of the yeast cell-cycle network by applying edge-removal, edge-addition, and edge-sign-switch mutations.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors found no exact algorithm for the same network control problem in more recent years. However, an algorithm for identification of the best one-bit perturbation is provided [35]. In this problem, a Boolean network is given and the problem is to find a gene that changing its initial state 1) does not change attractors of the network, 2) maximize the size of the basin of some desired attractors.…”
Section: Introductionmentioning
confidence: 99%
“…The main obstacle for methods based on matrix perturbation theory is that operations on the probability transition matrix (2n×2n) are too time‐consuming, where n represents the gene number. In 2016, Hu et al [11] proposed an efficient algorithm which updated the state‐transition diagram based on the basin‐of‐states (BOS) of the perturbed states. The BOS of a state represents the number of states which can flow into it.…”
Section: Introductionmentioning
confidence: 99%